Baler - Iglesias, Roy; Salvdor, Phillip; Cutis, Anne; Rosales, Jericho; Meily, Mark; Viva Films (Firm). ([Pace of production not identified] Viva Films, 2008)
"Baler is a love story between Feliza, the daughter of a rebel commander and Celso, a half-Spanish soldier, set during the twilight years of the Spanish regime in the Philippines. The young couple struggle to keep their forbidden love alive despite familial and political tensions, culminating in an almost year-long blockade known as the Siege of Baler."
"Summary taken from https://www.imdb.com/title/tt1305656/plotsummary?ref_=tt_ov_pl
Produced by Vic del Rosario; music by Vincent de Jesus; cinematography by Lee Meily.
Phillip Salvador, Jericho Rosales, Anne Curtis.
DVD
In Tagalog
Keywords: Drama; Romance